IOP and investment in defence and fossil fuel. (1st November 2022) - Tsoumpas, Charalampos; Povey, Megan; Barnham, Keith; Bassant, Martin; Eisenhandler, Eric; Tibbits, Tom; Watson-Parris, Duncan
Abstract : Letters criticising the Institute of Physics (IOP) for holding investments in arms companies involved in the nuclear weapons industry, and in fossil fuels.